CD4 Variability in Malawi: Implications for Use of a CD4 Threshold of 500 Cells/mm3 Versus Universal Eligibility for Antiretroviral Therapy. (29th August 2016) - Schooley, Alan L.; Kamudumuli, Pocha Samuel; Vangala, Sitaram; Tseng, Chi-hong; Soko, Chifundo; Parent, Julie; Phiri, Khumbo; Jahn, Andreas; Namarika, Dan; Hoffman, Risa M.
Abstract : Our data show low accuracy of a single CD4 count for individuals with observed CD4 counts of 350-650 cells/mm 3 . We hope our data will be interesting to programs making decisions around continued use of CD4 thresholds versus adopting WHO universal eligibility for ART. Abstract: Background.  Given the uncertainty about the ability of a single CD4 count to accurately classify a patient as antiretroviral therapy (ART) eligible, we sought to understand the extent to which CD4 variability results in misclassification at a CD4 threshold of 500 cells/mm 3 . Methods.  We performed a prospective study of CD4 variability in Malawian human immunodeficiency virus-infected, ART-naive, World Health Organization (WHO) stage 1 or 2, nonpregnant adults. CD4 counts were performed daily for 8 days. We fit a Bayesian linear mixed-effects model of log-transformed CD4 cell counts to the data. We used Monte Carlo approximations to estimate misclassification rates for different observed values of CD4. The misclassification rate was calculated based on the conditional probability of true CD4 given the geometric mean of observed CD4 measurements. Results.  Fifty patients were enrolled from 2 sites. The median age was 33.5 years (interquartile range, 27.5–40.0) and 34 (68%) were female. Misclassification rates were <1% when the observed CD4 counts were ≤250 or ≥750 cells/mm 3 . Rates of misclassification were high at observed CD4 counts between 350 and 650 cells/mm 3, particularly when a single measurement was used (up to 46.7%). Conclusions.  Our data show that ART eligibility based on a single CD4 count results in highest risk of misclassification when observed CD4 counts are in the range of 350–650 cells/mm 3 . Given the benefits of early ART, countries should weigh the costs and complexity of CD4 testing using a 500 cell/mm 3 threshold against the cost savings and public health benefits of universal eligibility.